Anomalous wrinkle propagation in polycrystalline graphene with tilt grain boundaries. Issue 5 (18th January 2023) - Zhao, Zihui; Wang, Yafei; Wang, Changguo
Abstract : The tilt grain boundaries can be used to absorb energy and shield dynamic wrinkle propagation. Abstract : Understanding the propagation of dynamic wrinkles in polycrystalline graphene with grain boundaries (GBs) is critical to the practical application of graphene-based nanodevices. Although wrinkle propagation behavior in pristine graphene (PG) and some defect-containing graphene samples have been investigated, there are no studies on the dynamic behavior of graphene with tilt GBs. Here, nine tilt GBs are constructed in graphene, and molecular dynamics (MD) simulations are performed to investigate anomalous wrinkle propagation. The MD simulation results show that a larger misorientation angle α first enhances the shielding effect of tilt GBs on wrinkle propagation before it weakens. The maximum Δ z root mean square (RMS) shows that a greater misorientation angle α first increases the maximum RMS of the GB region (RGB ) before it then decreases, while the maximum RMS of R80 exhibits the opposite trend. Moreover, approximately 96% of the C60 kinetic energy is converted into kinetic and potential energies in graphene, and the potential energy in graphene presents two evolution modes. Phase diagrams are plotted to study the effect of the distance d 1 and rotation angle β on the wrinkle propagation and sensitivity of the maximum RMS value to d 1 . It is expected that our results can provide a fundamental understanding of defect engineering and guidelines to design protectors, energy absorbers, and defect detectors in nanodevices.